IMMIGRANTS ON A THEORETICAL PATH OF NEW MEDIA AGENDASETTING: WEBSITES COVERAGE AND ITS IMPACT ON THE STRUCTURE OF SOCIETY TOWARDS IMMIGRANTS - Hussein Saadi Mohammed Ali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper aims to clarify the impact of the agenda-setting of websites on the structure of societies towards immigration. Community structure and agenda-setting theories are the conceptual reflections of each other that are seldom considered side by side. Through this paper, we will provide modest evidence on the agenda-setting for immigrant issues in the new media, due to some studies and researches that have provided strong evidence of shifts in tone and discourse indicating the influence of the media on a structured society. However, it did not clarify how it can influence the structure of a single, demographically diverse society. This paper provides a conceptual presentation based on the arguments and academic evidence by providing an adequate explanation showing the mechanism of the media agenda’s impact on the structure of societies towards the migration to Europe, as an establishment of a model that helps journalists and workers in the media field to understand how to utilize the new media impact on societies.